Stroke and Recurrent Thrombosis of the Coronary Arteries Probably due to Patent Foramen Ovale and Antebrachial Vein Thrombosis in Patient with STEMI – Case Report - Konopka, Anna; Marzec, Karolina; Paschalis-Purtak, Katarzyna; Demkow, Marcin; Zalewska, Joanna; Smaga, Elżbieta; Michałowska, Ilona (Acta medica Lituanica, 2026)
74- years old woman with history of cryptogenic stroke in 2010 (during hospitalisation at neurological department possible reasons of stroke were excluded at that time),  with less than one year history of paroxysmal atrial fibrillation (AF) treated with apixaban, hypertension, diabetes type II, hypothyreotocsicosis and obesity was admitted to our hospital twice. For the first time admitted due to ST segment elevation myocardial infarction (STEMI) and episode of AF. Coronary angiography revealed occlusion of left circumflex coronary (LCX) artery and percutaneous coronary intervention (PCI) with stent implantation was performed.  Conversions of AF episodes to sinus rhythm were spontaneous. Patient was discharged home and admitted once again three days after discharge. STEMI of anterior wall and a new episode of AF  was diagnosed. Immediate plain old balloon angioplasty (POBA) with implantation of an additional stent in left anterior descending coronary artery  (LAD) was performed. Sixty minutes after  procedure, the patient developed symptoms of  mild right-sided pyramidal syndrome and slight aphasia. Patient’s status was  assessed on 3 points according to the National Institutes of Health Stroke Scale (NIHSS) and patient was not qualified for thrombolysis and mechanical thrombectomy of cerebral artery.  Four days after symptoms of stroke, CT did not reveal new significant lesions of the brain and 8-th days after stroke aphasia almost completely disappeared.  Thrombus in the left atrium appendage was excluded and patent foramen ovale (PFO) with left to right flow was revealed. Due to the risk of reverse flow as a possible reason of strokes (now and 15 years ago) and recurrent thromboembolisation of coronary arteries and presence of thromboembolisation of antebrachial vein the successful occlusion of PFO with Amplatzer Septal Occluder was performed. In good condition, patient was discharged home.
Keywords: stroke; myocardial infarction